The Problem of an Author in Contemporary Theatre Publicism in Ukraine: Psycholinguistic Aspect - Halatska, Valentyna (East European Journal of Psycholinguistics, 2014)
The article studies the realization of a communicative act (theatre reality – journalist reader) through the forms of author’s consciousness expressing. Esthetic and communicative effect, which is realized through particular psycholinguistic means and produces effective form of intercultural dialogue, is analysed. In today’s Ukrainian journals media aspect of theatrical art is represented in the active out – of- subject forms of expressing author’s consciousness. These forms can be found in informational (short article, dialogue interview, portrait-interview) and analythical (review) genres, style peculiarities of the materials and others. Formal and subject arrangement of theatrical publicism is characterized by methaphorical vision of theatrical reality and dialectical description of the material. Subject arrangement of the works of today’s theatrical publicism in Ukraine expressed in the genres of interview in which the main notions of K. Stanislavskyi’s system are transformed into psycholinguistic definitions of “motive”, purpose and “activity script”. The research of the forms of expressing author’s consciousness in theatrical publicism in today’s Ukraine is considered to be prospective because of the productivity of interdiscipline approach to the problem, as well as, the back of analyses of the theory of art social communication. References Аristotel. (1967). Poetica [Poetics]. Kyiv: Mystetstvo. Balme К. (2008). Vstup dо Teаtrоznаvstvа [An Introduction to Theatrical Studies]. Lviv : LVNTL-Кlаssiка. Bаkhtin, M. (1986). Estetika Slovesnogo Tvorchestva [The Asthetics of Theatrical Creativeness]. Мoscow: Iskusstvo. Voroshilov, V. (2001). Zurnalistika [Journalism]. S.-Petersburg: Mikhaylov Publishers. Dоlеnkо, V. (2009). Gоlоs Еdіth Pіаf [Voice of Edith Piaf]. Кіno–Tеаtr, 1, 7. Кlеkоvkіn, О. (2002). Sакrаlnuy tеаtr: Gеnеzа. Fоrmy. Pоеtikа [Sacred Theatre: Genesis. Forms. Poetics]. Кyiv: Kyiv State Institute of Theatrical Art. Коrmаn, B. (1974). Literaturovedcheskye terminy po probleme avtora [Literary Studies Terms on Author Problem]. Izhevsk: Udmurtia Univ. Kotte, A. (1995). Theater der Region – Theater Europas. Basel: Kongress der Gesellschaft fur Theaterwissenschaft. Кurbаs, L. (2001). Phіlosоphia teatry [The Philosophy of Theatre]. Кyiv: Оsnоvy. Lеоntyev, А. (2003). Оsnоvy Psikholingvistiki [The Foundations of Psycholinguistics]. Мoscow: Smysl. Pеlаgеsha, N. (2008). Uкrаinа у Smyslоvykh Viynakh Postmodernismu [Ukraine in Semantic Wars od Postmodernism]. Кyiv: Natsionalnyi. Institut Strategichnykh Doslidzhen. Pelypenko, А, Yakovenko, I. (1998). Кulturа Kаk Systema: Strukturnаya Mоrphоlоgiya Kultury [Culture as System: Structural Morphology of Culture]. Мoscow: Yazyki Russkoy Kultury.